Corrective osteotomies around the knee joint using hexapods Kniegelenknahe Korrekturosteotomien mittels Hexapoden - Dickschas, Jörg (Operative Orthopadie und Traumatologie, 2023)
Objective: Correction of deformities around the knee joint in the frontal and sagittal axis, torsion, length and translation. Indications: Complex deformities of the proximal tibia, and to a lesser extent of the distal femur, which cannot be treated with acute correction using plate or nail osteosynthesis. Contraindications: Nicotine abuse, soft tissue problems, lack of patient compliance. Surgical technique: First, mounting of the proximal ring of the ring fixator strictly parallel to the joint line in 2 planes, fixation with 3 or 4 pins or wires. Then mounting of the distal ring, fixation also with 3 or 4 wires, connection of both rings with 6 struts (movement units with which the length can be adjusted). Then the fibula osteotomy is performed in the transition from the distal to the middle third, and finally the tibial osteoclasia is performed via a mini-incision as a drill hole chisel osteotomy in the CORA (center of rotation and angulation) of the malposition. Postoperative management: Immediately postoperatively, the deformity is defined usimg computer software, the exact position and size of the ring and struts are entered, and a knee image is taken in 2 planes with X‑ray signal adapter (beacon) on the ring fixator to plan the continuous correction. Thereupon continuous correction of the deformity via daily rotation on the 6 struts, which is done by the patients themselves at home after the hospital stay. At the time of correction, pain-adapted partial weight-bearing with 20 kg up to half body weight. After completion of the correction, repeat X‑ray diagnosis and check whether the correction goal has been achieved. If necessary, reprogram a program for renewed continuous correction if residual deformity remains. When the correction goal is reached, X‑ray check. After 6 weeks, with bony consolidation, gradual loading. The treatment of the correction can either be carried out in the ring fixator (wearing time of 0.5–1 year not unusual) or secondarily via a change of procedure to plate osteosynthesis. Results: We report on 25 knee joint corrections in 23 patients (12 women and 11 men) using hexapods (Taylor spatial frame) during the period 2016–2023. One patient had a femoral and a tibial fixator at the same time; another patient had a triple fixator at the tibia. The mean age was 32 (6–73) years. 15 left and 10 right corrections were performed. 19 fixators had been applied tibial, 5 fixators femoral, and 1 fixator cross-jointly (for contracture). The indications were 6 congenital complex deformities, 10 posttraumatic complex deformities, 3 pseudarthroses after correction osteotomies, 2 patients with osteomyelitis, 1 knee contracture and 1 infection after fracture osteosynthesis with nails. The forms of correction performed were varizations and valgizations in frontal axis, extension and flexion in sagittal plane, torsional corrections, lengthening also after acute shortening (pseudarthrosis resection) and segmental transport. Acute shortening without lengthening was also treated with the fixator only until bone healing and a Masqualet procedure was bridged with it. The average duration of fixator wear was 144 (31–443) days. All patients were followed up until final metal removal. There were 19 change of procedure to another osteosynthesis procedure (18 plate osteosynthesis, 1 ESIN); 6 times the treatment in TSF (Taylor Spatial Frame) was performed until final bone healing.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Complex deformity; Continous correction; External fixation; Posttraumatic deformity; Taylor spatial frame